The Renaissance: A Cultural Revolution that Transformed History (Eurasian Journal of Humanities and Social Sciences, 2023)
The Renaissance, a period spanning roughly from the 14th to the 17th century, stands as a pivotal epoch in human history. Often dubbed as a "Cultural Revolution," this transformative era reshaped the intellectual, artistic, and scientific landscapes, laying the groundwork for modernity. Let's delve into the key aspects of the Renaissance, exploring its profound impact on various facets of society